Responsibility and Accountability in the World of Futures Trading: Analysis of Futures Brokers and Broker Representatives Under the Spotlight of Civil Law and BAKTI Arbitration" - Rahman, Muhammad Sabir; Efendi, Syamsul; Amboro, Yudhi Priyo; Simanjuntak, Kristi W; Elfikri, Nurul Fazri; Rohani, Aceng Asnawi; Agus, Dede (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to examine the role of Article 1367 of the Civil Code in determining the duties of Futures Brokers and Futures Broker Representatives in the context of Indonesian commodity futures trading, with a focus on the consequences for violations of these duties by Futures Broker Representatives. respond to it. This methodology is based on normative legal principles and is based on research into relevant literature and examination of BAKTI rulings in the field of commodity futures trading arbitration. Findings from this study highlight the importance of taking into account the Futures Broker Representative's level of professionalism as well as any applicable rules and regulations when determining the extent to which the Futures Broker is legally liable for the Futures Broker Representative's conduct. In order to provide fairness and clarity in commodity futures trading, this study's findings suggest that current rules need to be revised and adjusted. The study also suggests directions for future research on the dynamics of futures trading's legal aspects.